Reference experimental tests to be used to validate numerical results in sheet metal forming - A. Santos (2004)
Finite Element modelling of sheet metal forming processes has still been experiencing a lot of improvements in recent years and this is the reason why its validation with reliable experimental results is very important. In order that experimental results are reliable and shall be a reference data, they need to be tested to repeatability and need to be obtained with such characteristic preferably by different institutions. In this paper two benchmarks are used to present experimental results obtained by different institutions as well as simulation results of the same benchmarks. Different materials are used, namely two aluminium alloys (Al5182-O and Al6016- T4) and two steels (DC06 and DP600).